Structural Characterization of Mycobacterium abscessus Phosphopantetheine Adenylyl Transferase Ligand Interactions: Implications for Fragment-Based Drug Design - Thomas, Sherine E.; McCarthy, William J.; El Bakali, Jamal; Brown, Karen P.; Kim, So Yeon; Blaszczyk, Michal; Mendes, Vítor; Abell, Chris; Floto, R. Andres; Coyne, Anthony G.; Blundell, Tom L. (Frontiers in Molecular Biosciences, 2022)
Anti-microbial resistance is a rising global healthcare concern that needs urgent attention as growing number of infections become difficult to treat with the currently available antibiotics. This is particularly true for mycobacterial infections like tuberculosis and leprosy and those with emerging opportunistic pathogens such as Mycobacterium abscessus, where multi-drug resistance leads to increased healthcare cost and mortality. M. abscessus is a highly drug-resistant non-tuberculous mycobacterium which causes life-threatening infections in people with chronic lung conditions such as cystic fibrosis. In this study, we explore M. abscessus phosphopantetheine adenylyl transferase (PPAT), an enzyme involved in the biosynthesis of Coenzyme A, as a target for the development of new antibiotics. We provide structural insights into substrate and feedback inhibitor binding modes of M. abscessus PPAT, thereby setting the basis for further chemical exploration of the enzyme. We then utilize a multi-dimensional fragment screening approach involving biophysical and structural analysis, followed by evaluation of compounds from a previous fragment-based drug discovery campaign against M. tuberculosis PPAT ortholog. This allowed the identification of an early-stage lead molecule exhibiting low micro molar affinity against M. abscessus PPAT (Kd 3.2 ± 0.8 µM) and potential new ways to design inhibitors against this enzyme. The resulting crystal structures reveal striking conformational changes and closure of solvent channel of M. abscessus PPAT hexamer providing novel strategies of inhibition. The study thus validates the ligandability of M. abscessus PPAT as an antibiotic target and identifies crucial starting points for structure-guided drug discovery against this bacterium.